Sandy's circus : a story about Alexander Calder - Stone, Tanya Lee (Viking, 2008)
As a boy, Sandy was always fiddling with odds and ends, making objects for friends. When he got older he started creating wire sculptures. Sandy made a lion. Next came a lion cage. Before he knew it, he had an entire circus and was traveling between Paris and New York performing a brand-new kind of art for amazed audiences.